2019
DOI: 10.3390/molecules24183387
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Dynamics Simulation of Protein β-Tubulin and Antifungal Cyclic Lipopeptides

Abstract: To elucidate interactions between the antifungal cyclic lipopeptides iturin A, fengycin, and surfactin produced by Bacillus bacteria and the microtubular protein β-tubulin in plant pathogenic fungi (Fusarium oxysporum, Colletrotrichum gloeosporioides, Alternaria alternata, and Fusarium solani) in molecular docking and molecular dynamics simulations, we retrieved the structure of tubulin co-crystallized with taxol from the Protein Data Bank (PDB) (ID: 1JFF) and the structure of the cyclic lipopeptides from PubC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…Previous findings have indicated that the presence of more polar metabolites, such as naphthoquinones and phenolics, can enhance the antioxidant activities of A. officinalis plant components [ 42 ]. A study also reported that this mangrove plant had a less toxic effect on Vero cell lines [ 43 ], which significantly supported our present investigation, in which the LC 50 value determined by the brine shrimp lethality was less than 250 µg/mL [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous findings have indicated that the presence of more polar metabolites, such as naphthoquinones and phenolics, can enhance the antioxidant activities of A. officinalis plant components [ 42 ]. A study also reported that this mangrove plant had a less toxic effect on Vero cell lines [ 43 ], which significantly supported our present investigation, in which the LC 50 value determined by the brine shrimp lethality was less than 250 µg/mL [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…Trajectories analyses were performed using the CPPTRAJ modules (Roe & Cheatham, 2013. Authors analyzed different trajectories like root mean square deviation (RMSD), a root mean square fluctuation (RMSF), hydrogen bonds (HBs) obtained from the MD simulation along with the change in binding free energy calculation using the AMBER18 (Agarwal et al, 2019;Al-Refaei et al, 2020;Cob-Calan et al, 2019;Nazarian et al, 2015;Pola et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…RMSD trajectory is used to study structural stability of the protease with and without the compound as in Equation ( 2), while RMSF trajectory helps to investigate the flexibility in the presence or absence of compound (Cob-Calan et al, 2019). These values were calculated by using the following equations:…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several reports have already been initiated on the structure prediction and their possible interaction with different cellular protein/enzyme targets [207][208][209][210]. Cob-Calan et al [211] demonstrated the interactions of the cyclic lipopeptides iturin A, fengycin, and surfactin with β-tubulin using molecular docking and molecular dynamics simulation. A comparative study had shown that iturin A and fengycin had higher binding affinity as compared to surfactin for the catalytic site of β-tubulin [210,211].…”
Section: Future Prospects Of Microbial Lipopeptides In Plant Disease mentioning
confidence: 99%
“…Cob-Calan et al [211] demonstrated the interactions of the cyclic lipopeptides iturin A, fengycin, and surfactin with β-tubulin using molecular docking and molecular dynamics simulation. A comparative study had shown that iturin A and fengycin had higher binding affinity as compared to surfactin for the catalytic site of β-tubulin [210,211]. With the help of advancements in genetic engineering and synthetic biology, improved lipopeptide production with higher efficiency could be developed, targeting important pathosystems.…”
Section: Future Prospects Of Microbial Lipopeptides In Plant Disease mentioning
confidence: 99%